2020
DOI: 10.1136/bmj.m4529
|View full text |Cite
|
Sign up to set email alerts
|

Clinical spectrum of coronavirus disease 2019 in Iceland: population based cohort study

Abstract: Objective To characterise the symptoms of coronavirus disease 2019 (covid-19). Design Population based cohort study. Setting Iceland. Participants All individuals who tested positive for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) by reverse transcription polymerase chain reaction (RT-PCR) between 17 March and 30 April 2020. Cases were identified… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
44
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 21 publications
8
44
1
2
Order By: Relevance
“…A combined analysis of all cases (identified either by PCR or serological testing) showed that the majority of patients had mild or asymptomatic disease, 19% required hospital admission (but subsequently recovered and were discharged), and the overall case fatality rate was 7% (substantially lower than the 30% mortality reported for the PCR-proven group). This provides a more Icelandic epidemiological study reported that, out of 1797 patients identified with SARS-CoV-2 infection (with a similar male:female ratio and average age to our patient cohort), 5.6% were hospitalised, 1.5% required admission to ITU and 0.6% died 1 . Further work is now needed to understand the role of different immunosuppressive treatments, the underlying disease for which they are prescribed, and co-morbidities, in determining COVID-19 outcome.…”
Section: Thus Identification Of Covid-19 Infection Based On Pcr Testsupporting
confidence: 64%
See 1 more Smart Citation
“…A combined analysis of all cases (identified either by PCR or serological testing) showed that the majority of patients had mild or asymptomatic disease, 19% required hospital admission (but subsequently recovered and were discharged), and the overall case fatality rate was 7% (substantially lower than the 30% mortality reported for the PCR-proven group). This provides a more Icelandic epidemiological study reported that, out of 1797 patients identified with SARS-CoV-2 infection (with a similar male:female ratio and average age to our patient cohort), 5.6% were hospitalised, 1.5% required admission to ITU and 0.6% died 1 . Further work is now needed to understand the role of different immunosuppressive treatments, the underlying disease for which they are prescribed, and co-morbidities, in determining COVID-19 outcome.…”
Section: Thus Identification Of Covid-19 Infection Based On Pcr Testsupporting
confidence: 64%
“…No epidemiological studies examining COVID-19 disease severity in the general population in London have been published for direct comparison. However, a recently published, large Icelandic epidemiological study reported that, out of 1797 patients identified with SARS-CoV-2 infection (with a similar male:female ratio and average age to our patient cohort), 5.6% were hospitalised, 1.5% required admission to ITU and 0.6% died 1 . Further work is now needed to understand the role of different immunosuppressive treatments, the underlying disease for which they are prescribed, and co-morbidities, in determining COVID-19 outcome.…”
Section: Discussionsupporting
confidence: 46%
“…In contrast to previous studies, which have focused on the fraction of infected who are severely ill [ 4 , [6] , [7] , [8] , [9] , 21 ], our cohort consisted mainly of non-hospitalized individuals, which also represents the majority of COVID-19 cases [ 22 , 23 ]. Thus, the data presented here is representative for the general population and the results have high external validity.…”
Section: Discussionmentioning
confidence: 99%
“…The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic represents an ongoing global health crisis of unprecedented scale [1][2][3] . While most patients experience asymptomatic or mild-tomoderate disease, some progress to experience more severe symptoms and may require hospitalization 4,5 .…”
Section: Introductionmentioning
confidence: 99%